Study on alternative technologies for the production of tomato during the rainy season in subhumid climate of Bahir Dar, Ethiopia - Alemayehu, Melkamu; Alemayehu, Getachew (Ethiopian Journal of Science and Technology, 2025)
Tomato production is not common during main rainy season, especially in sub-humid climatic conditions like in Bahir Dar. Therefore, an experiment was conducted to study the production potential of tomato using rainshelter and management practices during the 2013 rainy season (June-October) in Bahir Dar. The experimental treatments were laid down in split-plot-design at three replications, where with and without plastic rain-shelter were assigned as main plots and management practices (fungicide and stalking) as sub-plots. The results revealed that tomatoes grown in protected structure were significantly (P<0.01) longer (100.5 cm), had more branches (8.9) and flowered earlier (49.1 days) than those grown under open field condition with the mean values of 50.9 cm, 6.3 and 54 days, respectively. Incidence and severity of late blight and yield of tomatoes were also influenced significantly by growth conditions, management practices and their interactions. Tomatoes grown under rain-shelter structure produced significantly higher total fruit yield (31.3 t ha-1) and exhibited low disease incidence (16.7%) and severity indexes (26.7%) on leaves and as well as on fruits with the mean values of 22.4% and 37.9%, respectively. Similarly, sprayed and staked tomatoes produced the highest marketable (35.2 t ha-1) and total (41.8 t ha-1) fruit yields and exhibited significantly lower late blight incidence and severity. In rainshelter structure, the management practices had similar effects on both disease and yield parameters, where higher yield and lower late blight incidence and severity were generally observed. In open field condition, however, only sprayed and staked tomatoes exhibited lower late blight incidence (23.3%) and severity (24%) on leaves and fruits with the mean values of 39% and 40%, respectively. The highest marketable yield (36.4 t ha-1) obtained from such tomatoes in open field condition was statistically similar with the yield obtained from the corresponding treatment in rain-shelter structure (34.1 t ha-1). Generally, the present findings showed that rain-shelter technology reduced incidence of late blight and thus it can be used as alternative technology for the production of tomato during the rainy season in and around Bahir Dar. Moreover, tomato can also be produced in open field using improved management practices such as staking and spraying with appropriate fungicides against late blight and similar diseases. Further research is required to select tomato varieties suitable for rainshelter technology as well as to optimize frequency of pesticide applications as their application may have residual effect on fresh vegetables like tomato.